2018
DOI: 10.15654/tpk-170725
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of syringomyelia in clinically unaffected Cavalier King Charles Spaniels in Germany (2006–2016)

Abstract: Summary Objective: The aim of the study was to investigate the prevalence of syringomyelia in clinically unaffected Cavalier King Charles Spaniels (CKCS) in Germany. Material and methods: From 2006 to 2016 a total of 339 asymptomatic CKCSs from all over Germany were included. Age ranged from 3 months to 11 years (mean 3.72 years ± 2.17 years). T1- and T2-weighted magnetic resonance images of the head and cervical spine were obtained. Results: Overall, 163 out of 339 (48.1 %) CKCSs showed evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The study identified 7/12 dogs with syrinx of 2-6 mm (figure 3) and confirms the prevalence of SM in the breed, [17][18][19][20] and that, in proportion to the rest of the cranium, the hindskull is reduced with increased cephalic index (figures 1 and 2). Since the reduced caudal skull had already been proven 12 21 and purported to be recognised by some breed experts, it might provide greater guidance in judging criteria to avoid conformation extremes in breeding.…”
Section: Potential Impact Of Study On Breeding Selectionsupporting
confidence: 69%
“…The study identified 7/12 dogs with syrinx of 2-6 mm (figure 3) and confirms the prevalence of SM in the breed, [17][18][19][20] and that, in proportion to the rest of the cranium, the hindskull is reduced with increased cephalic index (figures 1 and 2). Since the reduced caudal skull had already been proven 12 21 and purported to be recognised by some breed experts, it might provide greater guidance in judging criteria to avoid conformation extremes in breeding.…”
Section: Potential Impact Of Study On Breeding Selectionsupporting
confidence: 69%
“…Not all studies had good control groups, especially the earlier ones. As SM occurs secondary to CM and is more likely in older dogs ( 34 , 35 , 45 , 46 ), it is important that the SM-clear cohort consists of dogs MRI scanned when older and typically aged 4 years or more. Equally it is important to accurately phenotype symptomatic dogs which can be challenging as the most common clinical sign is pain which is subjective and in the dog overly reliant on owner reporting ( 39 , 47 , 48 ).…”
Section: Current Understanding Of the Morphological Changes In Caninementioning
confidence: 99%
“…But these findings seem to suggest that CM/SM is, like in the CKCS, a socalled late onset disease. Such an association may be explained by skull conformation, maturation, and changes in craniocerebral morphology and syringomyelia already documented in several other studies for the CKCS (8,14,15,17,30,41,(44)(45)(46)(47). There are currently no specific studies that document objective information on skull maturation or craniocerebral morphology changes in the Pomeranian.…”
Section: Signalment Factors and Cm/sm Classificationmentioning
confidence: 67%